MAKNA SIMBOL RITUAL MENURUNKAN JALUR DI KABUPATEN KUANTAN SINGINGI - Liandi, Oksas; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Pathway culture in Kuantan Singingi Regency is a cultural tradition that has lasted from colonial times to the present, the tradition is pathway. This track is held annually to commemorate the Republic of Indonesia's Independence Day which is usually held in August every year. This pathway tradition is not only included in the Riau Province cultural tourism agenda but has also been included in the National cultural tourism agenda. Pacing this pathway has a cultural meaning contained therein, namely tenacity, cooperation, hard work, agility and sportsmanship. But behind it all without realizing the tradition of Pacu Path is loaded with magical practices or what is called shamanism. The practice of shamanism and forecasting is currently still believed by most of the Kuansing community in various ritual activities. Including lowering the lane, lowering lane in Kuantan singing can not be separated from the intervention of shamans or so-called magical. This magical practice has emerged at the beginning of the planning process and the process of making the path to the path has competed in the Batang Kuantan river arena every year.This study uses qualitative research methods, the technique of gathering informants used in this study is the Snowball technique, interview data collection techniques and documentation.The results of the research The process of lowering the pathway in Kuantan Singingi Regency there are 6 (six) stages, namely: a) Lane handlers install materials / offerings in the lane section. b) Path handlers surround the path. c) Pathers chant mantra / pray. d) Pray with the lane child. e) The lane handler determines the correct time to lane, to avoid the same time lane lane with other lanes, or competitors lane. f) After the time is set, the lane handler gives a signal to all lane children, so that the lane is ready to be lowered.Keywords: Meanings, Symbols, Paths.